Generation Perceptions and Interests of Millennials in Zakat Digitally in Medan City - Muhammad Anwar; Juliana Nasution; Nursantri Yanti (Journal of Applied Business Administration, 2025)
This study aims to analyze the relationship between perceptions and interests in digital zakat payments among millennials in Medan City. This is based on the rapid development of technology, finance, and zakat digitalization, which significant improvements have not yet matched in national zakat collection realization. This study employs a quantitative approach with a descriptive correlational design. The sample consists of 85 millennial respondents living in Medan City who have experience or knowledge of digital zakat platforms. Data were collected through a closed-ended questionnaire using a Likert scale and analyzed using validity, reliability, Pearson correlation, and linearity tests. The results indicate that millennials' perceptions of digital zakat fall into the positive category, with an average score of 65.92. Meanwhile, their interest is also classified as high, with an average of 48.16. The correlation analysis shows a positive and significant relationship between perceptions and interests in digital zakat (r = 0.563; p < 0.001). This confirms that stronger perceptions of the convenience, security, and benefits of digital zakat led to higher interest in paying zakat through digital channels. This research makes a significant contribution to designing more inclusive, educational, and relevant digital zakat collection strategies for millennials in the digital era.